AASCU president discusses her leadership journey. Issue 1 (22nd March 2022) - Takami, Lisa Mednick
Abstract : Mildred García, Ed.D., assumed the presidency of the American Association of State Colleges and Universities in January 2018. Previously, she served as President of California State University, Fullerton and Berkeley Colleges (New York and New Jersey campuses). In a recent interview, García shared a glimpse into her leadership journey along with words of advice for other leaders. The following excerpt of that interview has been edited for space and clarity.